Analysis Of Stock Return Anomaly On The Indonesia Stock Exchange Based On Market Capitalization - Btari Gavrilla Larasati; C. Ambar Pujiharjanto; Nilmawati Nilmawati (Journal of Business Innovation and Research, 2023)
There has been a well-known market anomaly in the stock market called the firm size effect. This theory explains that small-cap stocks may provide greater stock returns than big-cap stocks. This research aimed to test the firm size effect theory on 827 stocks listed on the Indonesia Stock Exchange (IDX) during January 2 to June 27, 2023. The research sample was divided into big-cap and small-cap categories based on the calculation of average market capitalization, then the average value of stock returns from both categories were statistically compared. The result showed that the average values of stock return from both categories were significantly different, but this finding did not support the hypothesis related to market anomalies, because the result showed that big-cap stocks provide a greater stock return compared to small-cap stocks. However, the top 10 small-cap stocks with the highest return showed a much greater value than the return of big-cap stocks. Therefore, investors may still choose to invest in small-cap stocks, especially for short-term investments.